Rapid material interrogation using X rays from a dense plasma focus - Ismail, Mohamed Ismail Abdelaziz Mohamed (Kansas State University, 2015)
Dense Plasma Focus (DPF) devices are multi-radiation sources of X rays, neutrons (when working with deuterium), ions, and electrons in pulses typically of a few tens of nanoseconds. The Kansas State University device (KSU-DPF) was commissioned to be used as a radiation source with the Mechanical and Nuclear Engineering Department. The device is operated by a 12.5 µF capacitor which can be charged up to 40 kV storing an energy of 10 kJ. The static inductance and resistance of the device L[subscript]0 and r[subscript]0 were measured to be 91±2 nH and 13±3 mΩ. Experiments have shown that the KSU-DPF device produces 2.45 MeV neutrons with a neutron yield of ~2 × 10^7 and 1.05 × 10^7 n/shots in both axial and radial directions. Ions up to 130 keV were measured using a Faraday Cup. The measured hard X-ray spectrum shows an X-ray emission in the range from 20 to 120 keV with a peak at 50 keV while the average effective energy was estimated, using a step filter method, to be 59±3 keV. The KSU-DPF device was used as a pulsed hard X-ray source for material interrogation studies using the signature-based radiation-scanning (SBRS) technique. The SBRS technique uses template matching to differentiate targets that contain certain types of materials, such as chemical explosives or drugs, from those that do not. Experiments were performed with different materials in cans of three sizes. Nitrogen-rich fertilizers and ammonium nitrate were used as explosive surrogates. Experiments showed 100% sensitivity for all sizes of used samples while 50% specificity for 5 and 1- gallon and 28.57% for quart samples. Simulations using MCNP-5 gave results in good agreement with the experimental results. In the simulations, a larger number of materials, including real explosives were tested. To ensure the feasibility of using the DPF devices for this purpose a second device was simulated and the results were encouraging. Experimental and simulation results indicate that use of DPF devices with simple, room-temperature detectors may provide a way to perform rapid screening for threat materials, especially for places where large number of packages need to be investigated.
Keywords: Dense plasma focus; X rays; Material interrogation; Engineering (0537); Nuclear Engineering (0552)